Method Development and Characterization of Liposomal Formulation of Isotretinoin - Md Iftekhar Ahmad; Punet Kumar; Sangam Singh; Nitin Kumar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to develop a liposomal drug delivery system of isotretinoin, an acne drug-using spray drying, as a cost-effective and time-effective technique. The liposomal formulation was prepared by using spray drying; three different strategies were adopted: suspension spray drying (SSD), thin-film hydration and spray drying (TFHSD), and emulsion spray drying (ESD). Isotretinoin was 99% bound with lipid, so lipids hydrogenated soy phosphatidylcholine (HSPC), distearoyl phosphatidylglycerol (DSPG), and cholesterol were selected for the formulation development. The HSPC, DSPG, cholesterol, and isotretinoin were taken in the ratio 4 : 1 : 0.16 : 3.1 mmol. In vitro drug release studies, microscopy, drug content, and related substance characterizations were done to formulate each strategy of spray drying prepared dry liposomes of isotretinoin. Results were compared with the USP monograph of isotretinoin. It was revealed that isotretinoin's liposomal formulation using ESD was having drug release according to the USP limits. Drug content was also according to the USP requirement; no free drug crystals were found in microscopy, multivesicular vesicles were found in shape, a particle size of up 60 µ was found. The ESD technique was a successful, time-effective, and cost-effective technique for preparing a liposomal drug delivery system for isotretinoin.